Volunteering During the COVID-19 Pandemic: Attitudes and Perceptions of Clinical Medical and Dental Students in Lagos, Nigeria - Adejimi, Adebola Afolake; Odugbemi, Babatunde Adeniran; Odukoya, Oluwakemi Ololade; Okunade, Kehinde Sharafadeen; Taiwo, Aminah Oluwatamilore; Osibogun, Akin (The Nigerian postgraduate medical journal, 2021)
Volunteering within the health-care sector is crucial during pandemics. This study aimed to assess the attitudes and perceptions of clinical medical and dental students in Lagos, Nigeria, about volunteering during the coronavirus disease 2019 (COVID-19) pandemic. A descriptive cross-sectional study was conducted amongst medical and dental students undergoing clinical postings at the two public universities in Lagos, Nigeria, using total population sampling. Data were collected using a web-based questionnaire and analysed using Statistical Package for the Social Sciences. Chi-square test and logistic regression analysis were used to test for association at the level of significance of 5%. The mean age of the respondents was 23.3 years ± 2.6 standard deviation and 62.5% were females. The majority (82.9%) of the respondents agreed to volunteer if provided with adequate personal protective equipment (PPE) and if adequately trained to do so (79.3%). Although perceived as dangerous, the majority (91.2%) of the respondents considered volunteering during the COVID-19 pandemic as a form of educational experience. Compared to the final-year students, penultimate year students were more likely to volunteer in the event of a health manpower shortage. The final-year students were more likely to volunteer if government made the request. Female students were more likely than male students to volunteer even if they were not compensated but would require parental approval. Medical and dental students perceived their involvement during the COVID-19 pandemic as a form of educational experience but would require adequate training and PPE. There is a need to train and provide adequate PPE for them to function as volunteers.